A switchable optical diffuser based on a polymer/nematic liquid crystal composite film with transient polymer balls-networks microstructure. Issue 15 (8th December 2019) - Zhou, Le; Han, Cheng; Saeed, Mohsin Hassan; Zhang, Cuihong; Zhang, Lanying
ABSTRACT: With the increasing development of multifunction liquid crystal displays (LCDs), multifunction optical diffusers have attracted more attention. In this work, switchable optical diffusers based on the transient polymer balls-networks in polymer/nematic liquid crystal composite films have been prepared and investigated, and the effects of thiol content, curing time, LC content and photo-initiator content on the polymer microstructures and optical properties of optical diffusers are systematically studied. An optical diffuser with the transient polymer balls-networks microstructure has achieved the high transmission (96.42%), high haze (90.49%), excellent optical diffusing ability and wide viewing angle of 150° (from −75° to 75°) on its off state. By the application of electric field of 40.0 voltage, the viewing angle of the optical diffuser turns to be narrower (from −60° to 60°), which gives great applications in tunable viewing angle devices and other electric optical devices. Graphical abstract: The transient polymer balls-networks microstructure in the LCs/polymer composite films not only provides the optical diffuser with high transmission and high haze, but the optical diffuser is also switched by the electric field due to the special structure. Additionally, the transient polymer balls-networks morphology is controlled via ene-thiol click reaction, which has great potential in the applications of LCs/polymer composite films.